melamore
melamore
12-07-2014
Mathematics
contestada
let f(x)=2x-6. solve f^-1(x) when x=2.
Respuesta :
konrad509
konrad509
12-07-2014
[tex]f(x)=2x-6\\ y=2x-6\\ 2x=y+6\\ x=\frac{1}{2}y+3\\ f^{-1}(x)=\frac{1}{2}x+3\\ f^{-1}(2)=\frac{1}{2}\cdot2+3\\ f^{-1}(2)=1+3\\ f^{-1}(2)=4 [/tex]
Answer Link
Ryan2
Ryan2
15-07-2014
a) Calculating f⁻¹(x)
[tex]y=2x-6\\ \\ x=2y-6\\ \\ 2y=x+6\\ \\ y=\frac{x+6}{2}\\ \\ \boxed{f^{-1}(x)=\frac{x+6}{2}}[/tex]
b) Calculating f⁻¹(2)
[tex]\boxed{\boxed{f^{-1}(2)=\frac{2+6}{2}=\frac{8}{2}=4}}[/tex]
Answer Link
VER TODAS LAS RESPUESTAS ( 83+ )
Otras preguntas
25/7 as a mixed number
what are the social and economic hardship settlers faced
during the reformation a Major criticism of the mediaval catgolic church was that it?
What would you find if you split open a pod of the cocoa tree
Write an expression that can be used to find 4x275 using mental math and properties of numbers
How did a drop in population affect the Roman Empire? A. It led to the abolition of slavery. B. It led to advancements in the medical field. C. It weakened the
how many ones are in 7 thousands
The distance from the center of a round table top to the edge of the table top is 4 ft. What is the area of the table top?
what are examples of Unicellular things in everyday life
Long term effects from the summit series 1972?